2018
DOI: 10.1063/1.5018488
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modal analysis of novel non-pneumatic mechanical elastic wheel based on FEM and EMA

Abstract: A combination of Finite Element Method (FEM) and Experiment Modal Analysis (EMA) have been employed here to characterize the structural dynamic response of mechanical elastic wheel (ME-Wheel) operating under a specific thermal environment. The influence of high thermal condition on the structural dynamic response of ME-Wheel is investigated. The obtained results indicate that the EMA results are in accordance with those obtained using the proposed Finite Element (FE) model, indicting the high reliability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In 2018, Zhao et al [34] study aimed to investigate the influence of high thermal conditions on the structural dynamic response of Mechanical elastic wheels (ME-Wheel) using a combination of FEM and Experiment Modal Analysis (EMA). The results showed that the EMA results agreed with those obtained using the FE model, indicating the high reliability of the proposed analysis method.…”
Section: Non-pneumatic Tire Modeling and Validationmentioning
confidence: 99%
“…In 2018, Zhao et al [34] study aimed to investigate the influence of high thermal conditions on the structural dynamic response of Mechanical elastic wheels (ME-Wheel) using a combination of FEM and Experiment Modal Analysis (EMA). The results showed that the EMA results agreed with those obtained using the FE model, indicating the high reliability of the proposed analysis method.…”
Section: Non-pneumatic Tire Modeling and Validationmentioning
confidence: 99%
“…An ME-Wheel consists of a hub, 12 hinge groups, five elastic rings, 12 snap rings, a flexible tire body, and other accessories, as shown in Figure 1. 811 The assembly process of an ME-Wheel is as follows. First, the elastic rings are twisted by steel wire and fixed through the snap rings evenly distributed along a circumferential direction.…”
Section: Structure Of Me-wheelmentioning
confidence: 99%
“…7 In the past, the static and dynamic characteristics of an ME-Wheel have been investigated deeply and its few potential advantages in some respects over a pneumatic tire were demonstrated in previous studies. 1,811 ME-Wheel not only have the basic functions of pneumatic tires but also eliminate the dangers of pressure deflating and blowouts, because the inflatable structure of a pneumatic tire is substituted by the flexible hinge groups. The structural design concept of ME-Wheel opens up a new route for safety tire techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This wheel does not require inflation, eliminating such safety problems as deflation and blowouts. The author’s research group has researched the performance of mechanical wheels, including their lateral deviation, roll, off-road, load-bearing and heat-transfer characteristics (Zhao et al , 2018; Wang et al , 2016b; Zang et al , 2015a; Zang et al , 2015b; Li et al , 2014; Du et al , 2017a; Du et al , 2017b).…”
Section: Introductionmentioning
confidence: 99%